‘Wired up about self’ - narcissistic traits predict elevated physiological arousal during self-disclosure in conversation - Koskinen E.; Henttonen P.; Harjunen V.; Krusemark E.; Salmi J.; Tuominen J.; Wuolio M.; Peräkylä A. (Elsevier, 2025)
Individuals vary in their self-disclosure motivations and physiological responses. It is unclear, however, whether the content of a person's self-view accounts for this variation. In this paper we explore the impact of self- disclosure on autonomic nervous system activity in participants with high and low levels of grandiose narcissistic traits. Three conversational experiments were conducted to simulate different contexts of self-disclosure: getting acquainted (Experiment 1), talking about emotional life experiences (Experiment 2), and telling emotional stories with varying self-relevance (Experiment 3). The experiments were conducted on the same sample of 22 dyads (n =44) measured in a single session. While Experiment 1 did not confirm the anticipated heightened sympathetic arousal in participants with high grandiose narcissism (N+), Experiment 2, focusing on telling about positive and negative life experiences, supported the hypothesis of increased skin conductance among the N+individuals. Experiment 3, with more specific topics that varied in self-relevance, further supported the notion that narcissism is associated with elevated physiological arousal during self-disclosure. Notably, the skin conductance of the N+individuals was particularly heightened when telling about being admired by others. Exploratory analyses showed that tellers' (whether N+or N-) skin conductance was even more pronounced when they were discussing with an N+ co-participant.